KERAGAMAN GENETIK 24 VARIETAS PADI SAWAH DAN PADI GOGO (Oryza sativa L.) INDONESIA BERDASARKAN MARKA SSR - Kristianto Nugroho; Slamet Slamet; Puji Lestari (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The use of molecular marker is an efficient approach to analyze the genetic diversity and it can be used widely in biological studies. The characterization of rice germplasms by using molecular markers technique is more precise because it is not influenced by environmental factors. The purpose of this study was to analyze the genetic diversity of 24 varieties of lowland and upland rice by using 15 SSR markers. The results showed as many as 86 alleles were detected in 24 rice varieties, with the average number of alleles per marker was 5.73 and the range of alleles per locus was 2-10. The average of major allele frequency was 43% with the lowest score was 26% on RM6997 and RM536 markers and the highest score was 65% on RM60 marker. A total of 14 SSR markers were able to discriminate heterozygous alleles within a range between 0.17 (RM105) to 1.00 (RM201, RM263, RM416, RM518 and RM223). The value of gene diversity ranged from 0.48 (RM60) to 0.81 (RM536) with an average of 0.70. The value of PIC (Polymorphic Information Content) ranged from 0.38 (RM105) to 0.78 (RM536) with an average of 0.65. The phylogenetic analysis showed that 24 rice varieties separate into two main clusters in the coefficient of 0.63. The first cluster consists of 12 lowland varieties and the second cluster consists of 12 upland varieties. The genetic diversity data in this study were expected could be a valuable information in the rice plant breeding activities in the future.